2007
DOI: 10.3846/1648715x.2007.9637563
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Information in the Hong Kong Forward Property Market

Abstract: Use of forward contracts for pre‐selling uncompleted properties is becoming popular in many countries. However, there have been limited researches investigating the risks arising from asymmetric information specific to buying a presale property and the critical factors required for the development of an effective forward property market. Hong Kong is one of the largest forward property markets in the world and it has been getting mature after half‐a‐century long development. This paper therefore aims to study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Transactions of uncompleted residential properties in Hong Kong were first recorded in 1954 at a housing estate of over a hundred blocks of three-floor buildings (Leung et al 2007a). After decades of development, presales have become a popular means of property disposal in the primary market.…”
Section: Hong Kong's Presale Systemmentioning
confidence: 99%
“…Transactions of uncompleted residential properties in Hong Kong were first recorded in 1954 at a housing estate of over a hundred blocks of three-floor buildings (Leung et al 2007a). After decades of development, presales have become a popular means of property disposal in the primary market.…”
Section: Hong Kong's Presale Systemmentioning
confidence: 99%
“…Given this, for the spot price distribution p ∼ [ p − δ, p + δ], we set the mean as p = 180 and the boundary range parameter as δ = 12. According to Leung et al (2007), one of the property presale payment schedules used in the US is a 5:95 system (that is, 5% deposit and 95% for later payments). We hence set the presale downpayment ratio as d = 5%.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…The studies suggested that with the demand side becoming the financial of the supply side in pre-letting and pre-sale market, buyers who are risk adverse would opt-out because of the market risk and capital finance risk that the arrangements transfer on them. Leung et al (2007) and Oloke et al (2017) mention the problem of housing space shrinkage, higher building defects, features mismatches and exaggeration of saleable areas as part of factors restricting the rate of adoption of the arrangements. Furthermore, Ibrahim et al (2015), Jadalhaq (2017) and Zhou et al (2018) identified fear of sudden development default or abandonment, lack of standardised real estate legislation/procedure and lack of perfect market information among factors impeding adoption of pre-letting and pre-sale financing arrangements.…”
Section: Introductionmentioning
confidence: 99%